If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(7 + -8x) = 46 (7 * -5 + -8x * -5) = 46 (-35 + 40x) = 46 Solving -35 + 40x = 46 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '35' to each side of the equation. -35 + 35 + 40x = 46 + 35 Combine like terms: -35 + 35 = 0 0 + 40x = 46 + 35 40x = 46 + 35 Combine like terms: 46 + 35 = 81 40x = 81 Divide each side by '40'. x = 2.025 Simplifying x = 2.025
| 3x+4(-3-6)=-55.3 | | x-3+y+8= | | 0.8*s+1=9 | | -24=-b+5b | | 3v-15v-15v=6 | | 120+.60x=60+.70x | | 16XY+144Z+32XY-2Z= | | 3v-15v-15v=-6 | | Hx^2+12-4hx-3x=0 | | cos(x)+cos(3x)=0.5 | | y=2(0.25)+5 | | 10p-20p-10p+18p=14 | | -8y+7=31 | | 5(4n+4)=-6 | | 5x-32+89=180 | | 7x+22= | | c=2x | | 4x+8x+16x+6x-x=11 | | X+17=56 | | 2a+s=294 | | 100-7r= | | -5x+2(x-3)=-2(x-3) | | 0.2x+10-6=1.2x+8 | | 7v-2v-v-3v=14 | | b+2+6=7 | | (-1)x(-3)= | | 4a+2s=588 | | -6-5x=-26 | | 15z-12z-2z=15 | | 3(6e-4)=e+4 | | 7(x+2)-5=7x+9 | | 4(10x-8)=x+9 |